Uncovering Metabolic Alterations in HCT-116 Colon Cancer Cells upon Exposure to Bamboo Leaf Extract Obtained from Guadua incana Londoño - Chitiva, Luis Carlos [UNESP]; Santamaría-Torres, Mary Andrea; Rezende-Teixeira, Paula; Borlot, Jessica Rodrigues Pereira de Oliveira; Romagna, Rodrigo de Almeida; Londoño, Ximena; Kitagawa, Rodrigo Rezende; Costa-Lotufo, Leticia V.; Prieto-Rodríguez, Juliet A.; Castro-Gamboa, Ian [UNESP]; Costa, Geison Modesti (MDPI, 2024)
Metabolic alterations are increasingly recognized as important aspects of colorectal cancer (CRC), offering potential avenues for identifying therapeutic targets. Previous studies have demonstrated the cytotoxic potential of bamboo leaf extract obtained from Guadua incana (BLEGI) against HCT-116 colon cancer cells. However, the altered metabolic pathways in these tumor cells remain unknown. Therefore, this study aimed to employ an untargeted metabolomic approach to reveal the metabolic alterations of the endometabolome and exometabolome of HCT-116 cells upon exposure to BLEGI treatment. First, a chemical characterization of the BLEGI was conducted through liquid chromatography coupled with mass spectrometry (LC-MS). Next, we assessed cell viability via MTT and morphological analysis using an immunofluorescence assay against colon cancer cells, and anti-inflammatory activity using an LPS-stimulated macrophage model. Subsequently, we employed LC-MS and proton nuclear magnetic resonance (1H-NMR) to investigate intra- and extracellular changes. Chemical characterization primarily revealed the presence of compounds with a flavone glycoside scaffold. Immunofluorescence analysis showed condensed chromatin and subsequent formation of apoptotic bodies, suggesting cell death by apoptosis. The results of the metabolomic analysis showed 98 differential metabolites, involved in glutathione, tricarboxylic acid cycle, and lipoic acid metabolism, among others. Additionally, BLEGI demonstrated significant nitric oxide (NO) inhibitory capacity in macrophage cells. This study enhances our understanding of BLEGI’s possible mechanism of action and provides fresh insights into therapeutic targets for treating this disease.
Keywords: anti-inflammatory activity; bamboo leaf extract; cytotoxic activity; endometabolome; exometabolome; Guadua incana; HCT-116 cells; metabolomics